2017
DOI: 10.21474/ijar01/2851
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Studies in Six Bivoltine Races of Bombyx Mori L., Based on Phenotypic Characters.

Abstract: Comparative studies of phenotypic characters in some developmental stages of mulberry silkworm, Bombyx mori. L was carried out in order to access their genetic diversity. Three Jam and three Pam races evolved in J&K were selected for the study. The egg, larvae and cocoon stage were studied for the various phenotypic and economic parameters; these qualitative and quantitative characters were put into various statistical analysis like correlation studies of length and weight changes during V instar and clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Genetic diversity is a fundamental criterion of animal and plant breeding programs because inter-and intra-population variability can be determined by recognizing the number of different forms of genotype expression and presented as information repositories in the form of genes, alleles and chromosomes (Pérez, 2010); the greater the variability found, the greater is the opportunity to find characteristics of interest, which in turn make up the genetic base, from which purpose-made, specific selection processes can be carried out for the objectives of an improvement program (Nezhad et al, 2010;Anuradha et al, 2012;Kumari and Tripathi, 2017).…”
Section: Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic diversity is a fundamental criterion of animal and plant breeding programs because inter-and intra-population variability can be determined by recognizing the number of different forms of genotype expression and presented as information repositories in the form of genes, alleles and chromosomes (Pérez, 2010); the greater the variability found, the greater is the opportunity to find characteristics of interest, which in turn make up the genetic base, from which purpose-made, specific selection processes can be carried out for the objectives of an improvement program (Nezhad et al, 2010;Anuradha et al, 2012;Kumari and Tripathi, 2017).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…These can give rise to hybrid combinations, descendants with high hybrid vigor, or transgressive individuals that can originate hybrids or commercial varieties (Lagos et al, 2003); it also allows estimation of rates of variation among genotypes, making it an effective tool for calculating increases in genetic potential in breeding programs (Nagaraju and Singh, 1997). Therefore, making a selection of genetically pure and divergent parental, knowing the genetic distances, and the nature and magnitude of the genetic diversity that exists among the available breeds of B. mori are critical activities because they determine the improvement of quantitative and qualitative traits linked to the production of cocoons (Sen et al, 1996;Nagaraju and Goldsmith, 2002;Maqbool et al, 2015;Kumari and Tripathi, 2017). Maqbool et al (2015) studied genetic divergence by analyzing quantitative traits in B. mori bivoltines and the results showed that 99.4% of the total divergence is represented by quantitative traits such as duration of fifth instar, total duration of larval cycle, weight of mature silk gland, cocoon weight, cocoon yield/10000 larvae, and denier.…”
Section: Genetic Diversitymentioning
confidence: 99%